Navigating the quantum-classical frontier - Bromley, Thomas R. (2017)
The description of a quantum system follows a fundamentally different paradigm to that of a classical system, leading to unique yet counter-intuitive properties. In this thesis we consider some of these unique properties, here termed simply the quantum. We focus on understanding some important types of the quantum: quantum coherence and quantum correlations, as well as quantum entanglement as an important subclass of quantum correlations. Our objective is to investigate how to quantify the quantum, what it can be used for, and how it can be preserved in the adverse presence of noise. These findings help to clarify the frontier between quantum and classical systems, a crucial endeavour for understanding the applications and advantageous features of the quantum world.